Peningkatan Hasil Belajar Siswa Melalui Pembelajaran Portofolio pada Mata Pelajaran PKN di SD Negeri 2 Uekuli Sulawesi Tengah - Nirwan Moara (Universitas Pendidikan Mandalika, 2020)
This study aims to improve student learning outcomes through portfolio learning in Class II PKN subjects SDN 2 Uekuli. The research method used was classroom action research with 15 students of class II SDN 2 Uekuli as the research subjects. The research instrument used observation sheets, questionnaires and tests. The data analysis technique used in this research was qualitative and quantitative descriptive analysis. The results of this study indicate that there is an increase in student activity and teacher performance in the learning process. The increase in the learning process has a positive effect on student learning outcomes, student outcomes have increased each cycle. Cycle I shows that classically students who have completed learning reached 25.58%, cycle II increased to 81.39%, then increased again in cycle III to 97.67%. The average learning outcomes also increased, in the first cycle was 53.05; cycle II increased to 73.49; and increased again in cycle III to 86.51. This shows an increase in students' understanding of learning material on children's rights at home and at school.